The effects of online education on the relationship between students and teachers in Chinese higher education institutions - Xiong, Luoying; Zychowicz, Piotr (Kultura-Społeczeństwo-Edukacja, 2023)
The advent of the internet has made online education more widely available and may have led to a creation of a new teaching model (Harasim, 2000). Online education’s convenience and multimedia options have also broadened the range of skills and courses that can be taught remotely. Online education continued to develop and grow throughout the 1980s and 1990s (Harasim, 2000) and with the ongoing evolution of technology, online education has become a distinct form of teaching and learning. In this context, China’s government initiated the ‘Online Education and Research Network Demonstration Project’ in 1994 (Jiang et al., 2023). In 2012, the trend of online education spread to the global higher education field, and internationally renowned MOOC platforms such as Udacity, Coursera, and EdX were gradually established (Pappano, 2012). It can be argued that the rapid expansion of online education empowers both students and teachers by breaking free from geographical and environmental constraints. However, anecdotal evidence suggests that many students and teachers are still uncertain about the quality and effectiveness of online courses and that it may negatively impact the teacher–student relationship. Also, online education may challenge traditional teacher-learner identities and relationships (Dai & Matthews, 2023). There are also concerns that factors such as limited interaction, time, location and participation may affect the teacher–student dynamic and relationship (Kang et al., 2006). Therefore, this article examines the impact of online education on the relationship between teachers and students in higher education institutions in China, using both quantitative and qualitative research methods. The quantitative research findings indicate that factors such as the communication platform used, student personality, and expectations surrounding the teacher–student relationship have different effects on the relationship. Additionally, qualitative research shows that factors such as course types and major choices have both positive and negative effects on the relationship between teachers and students in Chinese higher education institutions. This article also offers recommendations to help improve the relationship between teachers and students in the context of online education in China.